The Poetry of Garcilaso: Bucolic Tradition and the Invention of a Visual Signature. Issue 10 (25th November 2016) - Béhar, Roland
Abstract: This paper analyses how it is possible to use the concept of 'visual signature' for the reading of Garcilaso de la Vega's poetical works. The pun on the name of the poet, disseminated throughout his eclogues, becomes a kind of sphragis, in a way that can be derived from Ferdinand de Saussure's interpretation of anagrams and, more precisely, in the way Joachim Du Bellay theorized the praxis of the onomastic allusio .